HUBUNGAN KEKUATAN OTOT LENGAN DAN KOORDINASI MATA-TANGAN DENGAN KEMAMPUAN PASSING BAWAH DALAM PERMAINAN BOLA VOLI SISWA SMP NEGERI 1 PULAU LAUT TIMUR - M Imran Hasanuddin (STKIP Paris Barantai, 2017)
This research is a descriptive research type. This study aims to determine: (1) To determine whether there is a relationship of arm muscle strength with the ability of passing down on the game bolavoli students of SMP Negeri 1 Pulau Laut timur. (2) To find out whether there is an eye-hand coordination relationship with lower passing ability on bolavoli game of SMP Negeri 1 Pulau Laut timur students. (3) To find out whether there is a joint correlation of arm muscle strength and hand-eye coordination with lower passing ability in bolavoli game of SMP Negeri 1 Pulau Laut Timur students. Its population is Junior High School Student 1 Pulau Laut timur. The sample used is male students of SMP Negeri 1 Pulau Laut east as many as 30 people. The technique of determining the sample is by random selection by drawing method (Simple Random Sampling). Data analysis technique used is descriptive analysis and inferential analysis through program of SPSS 22 at significant level Î± 0,05. The results showed that; (1) there is a relationship of arm muscle strength with the ability of passing down on bolavoli game of students of SMP Negeri 1 Pulau Laut timur, 62.4%, (2) there is an eye-hand coordination relationship with lower passing ability in bolavoli game students SMP Negeri 1 Pulau The eastern sea, amounting to 27.2%, (3) there is a significant relationship jointly arm muscle strength and hand-eye coordination with the ability of passing down on the game bolavoli students of SMP Negeri 1 Pulau Laut timur, with the value of F: 38.439 and sig (p) = 0,000. Keywords: Arm Sleeve Strength, Hand-eye Coordination, bottom passing.